If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -3 + -4x = -24 Reorder the terms: -3 + 7x + -4x = -24 Combine like terms: 7x + -4x = 3x -3 + 3x = -24 Solving -3 + 3x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3x = -24 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = -24 + 3 3x = -24 + 3 Combine like terms: -24 + 3 = -21 3x = -21 Divide each side by '3'. x = -7 Simplifying x = -7
| .5(10x-20)=5x-10 | | -8x-15=17 | | (4u-3v)(-2w)= | | F(3)=2x-7 | | 6(m+1)=8(3+m) | | x^2+20x+35=5x-1 | | Y=6x^3-13x^2+4x+3 | | 3_/x-3=5 | | x^2-11x+27=9 | | 3/4x-5=23 | | 30=s+368 | | 2(x+1)+4=-12 | | -5x+4=-2x+7 | | 5x-4=x+13y | | h=-7t^2+56t | | -10x+5y=-5 | | 28x-6(3x-5)=40-5x | | K=2.500 | | 2(x-1)+3=x+a+1 | | X^2+16x+55=o | | (-3)=(x-2)(x-2) | | 10v+11=-5(2v+3)-1 | | Yw+Yv=x | | -9+6x=4(x-3)+15 | | -7(v+1)=-3v+1 | | 4n-12=2(-6+2n) | | x-x*.1=93 | | z^2-14z=-58 | | 13+g=27 | | 5(k-7)=25 | | 7x^2-12x-115=0 | | x+x*.1=93 |